Tribology of polymeric nanocomposites : friction and wear of bulk materials and coatings - Friedrich, Klaus, 1945-; Schlarb, Alois K. (Butterworth-Heinemann, 2013)
A practical guide to the tribological qualities and applications of polymeric nanocomposites for engineers and designers Provides a complete reference to polmer nanocomposite material use in tribology from preparation through to selection and use. Explains the theory through examples of real-world applications, keeping this high-level topic practical and accessible. Includes contributions from more than 20 international tribology experts to offer broad yet detailed coverage of this fast-moving field. Tribology of Polymeric Nanocomposites provides a comprehensive description of polymeric nanocomposites, both as bulk materials and as thin surface coatings, and provides rare, focused coverage of their tribological behavior and potential use in tribological applications. Providing engineers and designers with the preparation techniques, friction and wear mechanisms, property information and evaluation methodology needed to select the right polymeric nanocomposites for the job, this unique book also includes valuable real-world examples of polymeric nanocomposites in action in tribological applications. Provides a complete tribology reference from the preparation to the selection of polymeric nanocomposites for engineers and designersExplains the theory through examples of real-world applications, keeping this high-level topic practical and accessibleIncludes contributions from more than 20 international tribology experts and now updated to include the latest developments in this fast-moving field.
Previous edition: Oxford: Elsevier, 2008.
Keywords: Polymeric composites.; Nanostructured materials.; Tribology.; Polymers.; elektronické knihy; electronic books